2020
DOI: 10.1007/s40744-020-00240-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Collagen Derivatives in Osteoarthritis and Cartilage Repair: A Systematic Scoping Review With Evidence Mapping

Abstract: Introduction: There is currently no diseasemodifying drug for osteoarthritis (OA), and some safety concerns have been identified about the leading traditional drugs. Therefore, research efforts have focused on alternatives such as supplementation with collagen derivatives. The objective of this scoping review is to examine the extent, range, and nature of research, and to summarize and disseminate research findings on the effects of collagen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 92 publications
0
29
0
9
Order By: Relevance
“…Multiple collagen factors were also detected in the ECM-receptor interaction pathway in Figure 5 . Collagen is a vital component of cartilage composition and plays a crucial role in protecting cartilage tissues [ 58 60 ]. This finding suggested that the ECM-receptor interaction signaling pathway may also play a critical role in the mechanism underlying circRNA-regulated OA ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple collagen factors were also detected in the ECM-receptor interaction pathway in Figure 5 . Collagen is a vital component of cartilage composition and plays a crucial role in protecting cartilage tissues [ 58 60 ]. This finding suggested that the ECM-receptor interaction signaling pathway may also play a critical role in the mechanism underlying circRNA-regulated OA ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoartritis je najčešća bolest zglobova i jedno od glavnih javno-zdravstvenih pitanja tekućeg veka [22]. Zbog rastućeg očekivanog trajanja života, posebno u razvijenim zemljama, njegova globalna prevalenca se brzo povećava, što ga čini bolešću povezanim sa izuzetno visokim ekonomskim opterećenjem [22,23].…”
Section: Savremena Razmatranjaunclassified
“…Osteoarthritis is the most frequent joint disease and one of the main public health issues of the century [22]. Due to increased life expectancy, especially in developed countries, its global prevalence is rapidly rising, making it a disease linked to a very high economic burden [22,23].…”
Section: Naša Tačka Gledištamentioning
confidence: 99%
“…Oral collagen supplementation was found to lead to significant improvements in patients with moderate knee OA after short daily treatments with oral HA preparations, compared to placebo-treated controls (Guadagna et al, 2018). Current clinical data on oral HA products for the treatment of mild to moderate knee OA are promising, and cumulative findings appeared to support a more favourable role than not for collagen supplements in efforts to safely reduce mild to moderate OA pain of the hand, hip or knee and to improve physical function at short term (Aghamohammadi et al, 2020;Honvo et al, 2020;Liu et al, 2018;Marks, 2020), although the quality of evidence is very low (Liu et al, 2018).…”
Section: Intra-articular Hyaluronic Acid Injections and Oral Collagen Supplementationmentioning
confidence: 99%